Analisis Tren Kebakaran Hutan dan Lahan di Indonesia Periode Tahun 2015-2019 - Arisman Arisman (LPPM Universitas Mataram, 2020)
Forest and land fires are disaster events that continue to recur every year. This study aims to determine patterns / trends in the occurrence of forest and land fires in Indonesia. The method used in this study is a descriptive statistical analysis and spatial analysis. The results showed that the occurrence of forest and land fires had the same pattern where the maximum peak of forest and land fires occurred in September. Another trend shown in the last five years is forest and land fires are fluctuative in which the frequency of events increases, the number of provinces affected also increases, but the area of land affected has an average of around 24.3% of the land area of Indonesia. Spatial analysis result shown the pattern of hotspot occurred in main province consist of Central Borneo, West Borneo, South Sumatera, Riau and Jambi. From this study it can be seen that the problem of forest and land fires is still high and need attention from the government